A antropologia trinitária como fundamento para o diálogo no pensamento de Chiara Lubich - Faro, José Antônio (2013)
This work deals with the Trinitarian anthropology, which underlies the practice of the dialogue performed by Chiara Lubich. Initially, this research demonstrates how the thought on dialogue falls on the whole of her spirituality. It is in the space between her peculiar understanding of the Gospel and the social praxis that comes from it, that she develops her vision and her dialogue experience. Secondly, this work offers a synthetic presentation of the main cardinal points of her spirituality in relation to her life experience, as an existential space in which the experience of God is revealed. Thirdly, this work deepens the understanding of unity and Jesus forsaken − understood as the synthesis of Christ's cross event − as the way to pass the threshold of God s communion life: He who is unity and trinity. Fourthly, it puts into dialogue the writings of Lubich with contemporary theologians, and philosophers. This dialogue reveals how her writings develop a vision of reality that can be defined as Trinitarian ontology. Emphasizing the idea of the Self as communion, according to lubichian point of view, the dynamics of the Trinitarian relationship must go into the determination of the Self as itself. Therefore, the unit with the other is intrinsic to the individual identity, that is, the human being fulfills himself/herself in the communion. Effectively, this means that the idea of the Self as Trinity leads in a Trinitarian anthropology. The categories of this anthropology are individualized on the basis of the communion of God who is unity and Trinity. Specifically, from the characteristics of the Trinitarian relationship of unity and distinction in God, this research identifies the characteristics of a Trinitarian way of life, whose incarnation and explanation in the history of mankind is dialogue. Finally, this research demonstrates that, for Lubich, dialogue is not an activity that adds itself to the many different dimensions of human life, but the way to relate with each other according to the model of the Trinity, that is, the very realization of the relationality self of man